How CIOs Engage Boards on Digitisation: The Case of Financial Services Companies in South Africa - Madzime, Ishe T (Department of Information Systems, 2019)
Boards as custodians of companies have to understand and lead digital transformation. Chief Information Officers (CIOs) can assist with educating and advising the board on digital transformation, but how do CIOs engage boards on the matter? Digitisation is at the heart of the financial services companies. Accordingly, this dissertation focussed on companies in the financial services industry. The main research question for this dissertation is: how do CIOs of South African (SA) financial services companies engage boards on digitisation? A detailed literature review was conducted which suggested research questions on digitisation, the role of the board and the CIO’s, engagement between them, and performance. The interview schedule was based on the foregoing topics. The researcher adopted an interpretivist epistemological perspective to understand digitisation engagements from the perspectives of board members, non-IT executives, and CIOs. The researcher employed a qualitative research method to gain an in-depth understanding of the subject. Fifteen semi-structured interviews were conducted with board members, non-IT executives and CIOs from financial services companies. Six key themes emerged from the thematic analysis of the interviews, namely: digitisation, the board’s role, the CIO’s role, non-IT executives’ role, digitisation engagement, and value. It’s important to note that the non-IT executives’ role was an additional role that emerged from the thematic analysis, this role had not been discussed in the literature review. Non-IT executives owned strategy and owned digitisation initiatives. A new Chief Digital Officer (CDO) role also emerged from the thematic analysis as a sub-theme of the CIO’s role. The CDO’s mandate was to drive company-wide digitisation over and above the CIO’s role. Considering the six themes collectively, the three entities (boards, non-IT executives, & CIOs) have a key role to play pertaining to digitisation. The findings suggested that CIOs often engaged the board through board meetings, board committees, and ad-hoc engagements. CIOs often educated the board on digital technologies, digitisation opportunities and digitisation issues. Further, findings suggested that digitisation engagement influenced How CIOs Engage Boards on Digitisation: The Case of Financial Services Companies in South Africa - 2 - value (e.g. responding to digitisation opportunities & issues) rather than performance which was difficult to prove. The dissertation concludes with methodological, substantive and scientific reflections, and recommendations for practice and future research. The dissertation contributes to the growing body of knowledge on digitisation and demonstrates how the logic espoused in the Complex context of Snowden and Boone's (2007) Cynefin framework can be used to guide how CIOs and boards engage on digitisation.